DEVELOPMENT OF TRACER INFORMATION SYSTEM ON MEDICAL RECORD DOCUMENT - Beny Binarto Budi Susilo; Musparlin Halid; Ikhwan (UNIVERSITAS STEKOM, 2023)
The information system was based on existing problems. This information system was computerized where borrowing and returning medical records is no longer manual. The purpose of the information system was to make it easier for officers to record, borrow and return. This model of tracer information system development for medical record files uses the waterfall method which includes requirements analysis and definition, system and design software, for the next stage, namely Implementation and unit testing and operation and maintenance, which is not carried out.